HUBUNGAN LATAR BELAKANG EKONOMI KELUARGA DAN DUKUNGAN ORANG TUA TERHADAP PRESTASI BELAJAR MATEMATIKA - Kewa, Maria Geronsia Azi; Wijayanti, Rina (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2018)
Mathematics learning achievement is the learning outcome/ability achieved by students during and after completing mathematics lessons where the results are expressed in the form of numbers or other symbols. Learning achievement is influenced by several factors including family economic background and parental support. This research is quantitative research, the study population was all VII grade students of Boawae 1 Junior High School totaling 101 students. Sampling using simple random sampling, where researchers about 24% of the population to be selected as samples, so that the study sample amounted to 24 students. The stages of this research are data collection using a questionnaire then analyzing the data using Pearson product moment correlation. The data collection process uses questionnaire techniques. Research data were analyzed using Pearson product moment correlation. Based on this study, it can be concluded that There is an insignificant relationship between the family's economic background on the mathematics learning achievement because the value of rcount is 0.242 smaller rtable at a significant level of 5% that is 0.404 and there is a relationship between parental support for mathematics learning achievement because the rcount of 0.747 is greater than rtable at a significant level of 5% which is 0.404 and there is a jointrelationship between the family's economic background and parental support for mathematics learning achievement because the Fcount value of 14.701 is greater than Ftable at the 5% significance level of 3.47.